Procurement of Goods and Services and Supervision on Budget Absorption - Lantowa, Felmi D.; Ntuiyo, Iyut Sintia Dewi (Jurnal Akuntansi, 2026)
This study aims to analyze the impact of procurement of goods and services and supervision on budget absorption at the Public Works and Spatial Planning Agency (PUPR) of Gorontalo Regency. This study seeks to explain how the effectiveness of procurement and supervision can affect the level of public budget realization, which reflects the performance of regional financial management. This study uses a quantitative, survey-based approach. Primary data was collected through questionnaires distributed to 33 respondents and analyzed using multiple linear regression. Validity, reliability, and classical assumption tests were conducted to ensure the model's accuracy. The results show that procurement of goods and services has a positive but insignificant effect on budget absorption, while supervision has a positive and significant impact. Simultaneously, both significantly affect the effectiveness of budget absorption. These findings reinforce the view that efficient procurement management and adequate supervision are essential elements in supporting local government fiscal accountability.